Selective gas detection using composite oxides based on Cox Oy /MnO2–z - Yu. A. Stenkin; D. V. Sokolov (Омский научный вестник)
The article presents the results of a gas response study of oxide semiconductor layers based on cobalt and manganese oxides CoxOy /MnO2–z with different Co/Mn ratios. An analysis of the experiments shows that there is certain synthesis condition in which selectivity to hydrogen sulfide of composite oxide layers is high. In the detection of hydrogen sulfide, the composite Cox Oy/MnO2–z (2,5Co/5Mn) has the maximum gas response.